SaHsfA4c From Sedum alfredii Hance Enhances Cadmium Tolerance by Regulating ROS-Scavenger Activities and Heat Shock Proteins Expression - Chen, Shuangshuang; Yu, Miao; Li, He; Wang, Ying; Lu, Zhuchou; Zhang, Yunxing; Liu, Mingying; Qiao, Guirong; Wu, Longhua; Han, Xiaojiao; Zhuo, Renying (Frontiers in Plant Science, 2020)
Heat shock transcription factor (Hsf) family, an important member in plant stress response, appears to affect cadmium (Cd) tolerance in plants. In this study, we identified and functionally characterized a transcript of the Hsf A4 subgroup from Sedum alfredii. Designated as SaHsfA4c, its open reading frame was 1,302 bp long and encoded a putative protein of 433 amino acids containing a complete DNA-binding domain (DBD). Heterologous expression of the SaHsfA4c in yeast enhanced Cd stress tolerance and accumulation, whereas expression of the alternatively spliced transcript InSaHsfA4c, which possessed an intron and an incomplete DBD, resulted in relatively poor tolerance and low Cd accumulation in transgenic yeast. The function of SaHsfA4c under Cd stress was characterized in transgenic Arabidopsis and non-hyperaccumulation ecotype S. alfredii. In addition, SaHsfA4c was able to rescue the Cd sensitivity of an Arabidopsis athsfa4c mutant. Furthermore, SaHsfA4c reduced reactive oxygen species (ROS) accumulation and increased the expression of ROS-scavenger enzyme genes and Hsps in transgenic lines. According to these results, SaHsfA4c increases plant resistance to stress by up-regulating the activities of ROS scavenger and the expression of Hsps.